2021
DOI: 10.1039/d1cy00878a
|View full text |Cite
|
Sign up to set email alerts
|

Air oxidized activated carbon catalyst for aerobic oxidative aromatizations of N-heterocycles

Abstract: A simple “reagent-free” thermal air treatment turns active carbon into a mildly oxidized material with an increased quinoidic content that catalytically dehydrogenates saturated N-heterocycles to the corresponding aromatic compounds. Additional...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 56 publications
(71 reference statements)
3
36
0
Order By: Relevance
“…Our first concern was to determine whether rGO was acting as a true carbocatalyst or as a stoichiometric reagent. 36 First of all, we confirmed that dehydrogenation of THQ did not occur without rGO ( Table 1 , entry 1). In the presence of rGO, quinoline is obtained under different solvents and reaction conditions, indicating that the process is general.…”
supporting
confidence: 71%
See 1 more Smart Citation
“…Our first concern was to determine whether rGO was acting as a true carbocatalyst or as a stoichiometric reagent. 36 First of all, we confirmed that dehydrogenation of THQ did not occur without rGO ( Table 1 , entry 1). In the presence of rGO, quinoline is obtained under different solvents and reaction conditions, indicating that the process is general.…”
supporting
confidence: 71%
“…The performance of rGO as carbocatalyst in ADH of N -heterocycles was first evaluated using 1,2,3,4-tetrahydroquinoline (THQ, 1H ) as a model substrate under oxygen-free conditions (see Table , as well as Figure S1 in the Supporting Information (SI)). Our first concern was to determine whether rGO was acting as a true carbocatalyst or as a stoichiometric reagent . First of all, we confirmed that dehydrogenation of THQ did not occur without rGO (Table , entry 1).…”
mentioning
confidence: 63%
“…In light of this, the catalytic activity of untreated AC has been improved by increasing its oxygen content in the present authors' laboratory allowing to lower carbocatalyst loading in ODH aromatizations of N-heterocycles. 40 The key to achieve improved activity was to treat AC thermally in air. This strategy was first used in heterogeneous gas-phase ODH reactions by Pereira, Figueiredo et al which allowed to considerably improve yields in ethylbenzene dehydrogenation.…”
Section: Scheme 11 Ac Catalyzed Synthesis Of 3-acylamino or 3-amino-5...mentioning
confidence: 99%
“…42 Moreover, the mechanism was explored through both experimental kinetic studies and DFT calculations with o-benzoquinone and PQ as computational models for the carbocatalysts. 5,6,16,40 Scheme 13 Cascade synthesis of substituted quinolines via AC catalyzed aerobic oxidative electrocyclization of aldehydes and 2-vinyl anilines…”
Section: Scheme 11 Ac Catalyzed Synthesis Of 3-acylamino or 3-amino-5...mentioning
confidence: 99%
“…[23] In fact, there were also a few cases on the use of carbon catalyst for the oxidative dehydrogenation or acceptor less dehydrogenation of N-heterocycles to Nheteroarenes. [24][25][26][27] For example, Gong and co-workers reported that graphene oxide (GO) could catalyze the oxidative dehydrogenation of N-heterocycles, [27] but the method still required a considerable amount of Na 2 CO 3 as an additive and a high reaction temperature of 120 °C to improve the catalyst efficiency. Therefore, it is preferable to design a new carbon catalyst with high activity for the oxidative dehydrogenation of N-heterocycles without additives under mild conditions, but it still remains a great challenge.…”
Section: Introductionmentioning
confidence: 99%